Pengaruh Tax Planning, Aset Pajak Tangguhan, dan Tax Avoidance terhadap Manajemen Laba (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2022) - Puspito, Giovani Wibisono Chandra; Karlina, Lilis (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research discusses the influence of tax planning, deferred tax assets, and tax avoidance on earnings management, focusing on companies in the food and beverage sub-sector. The purpose of this study is to determine the simultaneous impact of tax planning, deferred tax assets, and tax avoidance on earnings management, as well as the partial influence of tax planning on earnings management, deferred tax assets on earnings management, and tax avoidance on earnings management. The chosen method for this study is a quantitative descriptive research method. The data used is secondary data, collected using documentation techniques. The sampling technique was conducted using purposive sampling based on criteria determined by the researcher. The data obtained were then analyzed using descriptive statistical analysis methods, panel data models, panel data regression model selection tests, classical assumption tests, panel data regression tests, and hypothesis tests. The research concludes that, simultaneously, tax planning, deferred tax assets, and tax avoidance influence earnings management. Partial testing concludes that tax planning does not affect earnings management, deferred tax assets significantly affect earnings management, and tax avoidance does not affect earnings management.